Kajian Teknis Loading dan Hauling Produksi Overburden pada Tambang Terbuka PT. Allied Indo Coal Jaya, Parambahan, Sawahlunto - Yosi Fermila Zarly; Tamrin Kasim (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract.PT. Allied Indo Coal Jaya is one of the mining companies located in the Parambah area, sawahlunto. In coal mining activities, PT. Allied Indo Coal Jaya uses open pit mining methods.PT. Allied Indo Coal Jaya targets overburden production for the eastern central pit at 35,000.00 bcm/month. Mining process for overburden material using mechanical equipment 1 komatsu pc 300-8 excavator unit with 3 hino fm 260 dump trucks from the loading point to a disposal distance of 750 meters.The problem that occurs is that the production of loading equipment and transportation equipment has not been fulfilled so that the production target has not been reached. Not achieving production due to the amount of work time wasted due to work barriers, both avoidable and avoidable obstacles.With these constraints, it will reduce the effective working time causing low work efficiency.Efforts to increase production can be done by increasing effective working time, available working time and increasing the number of transportation equipment to become four dump truck hino fm 260 units with production from 23.351,78 bcm / month to 36.571,82 bcm / monthWith the improvement of effective working hours and increased production from the increasing number of transportation equipment, the production target is achieved.To be able to achieve the production target, it is better to monitor the work time that has been set in order to prevent obstacles that occur during work and the need to calculate the standard time barriers, so as to facilitate control.Keywords:Overburden, work efficiency, effective working hours.Abstract.PT. Allied Indo Coal Jaya is one of the mining companies located in the Parambah area, sawahlunto. In coal mining activities, PT. Allied Indo Coal Jaya uses open pit mining methods.PT. Allied Indo Coal Jaya targets overburden production for the eastern central pit at 35,000.00 bcm/month. Mining process for overburden material using mechanical equipment 1 komatsu pc 300-8 excavator unit with 3 hino fm 260 dump trucks from the loading point to a disposal distance of 750 meters.The problem that occurs is that the production of loading equipment and transportation equipment has not been fulfilled so that the production target has not been reached. Not achieving production due to the amount of work time wasted due to work barriers, both avoidable and avoidable obstacles.With these constraints, it will reduce the effective working time causing low work efficiency.Efforts to increase production can be done by increasing effective working time, available working time and increasing the number of transportation equipment to become four dump truck hino fm 260 units with production from 23.351,78 bcm / month to 36.571,82 bcm / monthWith the improvement of effective working hours and increased production from the increasing number of transportation equipment, the production target is achieved.To be able to achieve the production target, it is better to monitor the work time that has been set in order to prevent obstacles that occur during work and the need to calculate the standard time barriers, so as to facilitate control.Keywords:Overburden, work efficiency, effective working hours.